Intricately carved Makara Torana - Temples of India Project Team (Jio Institute, 2024)
A notable characteristic of this temple is the intricate carving of makara toranas (ornamental gateways/arches crafted with mythical crocodile creatures flanking on both ends) crowning the central four pillars of the mandapa (pillared hall) of the Undeshwar Temple. These toranas significantly enhance the beauty of the mandapa.